Mucosal Genes Expression in Inflammatory Bowel Disease Patients: New Insights - Sumaiah J. Alarfaj; Sally Abdallah Mostafa; Walaa A. Negm; Thanaa A. El-Masry; Marwa Kamal; Mohamed Elsaeed; Ahmed Mohamed El Nakib (MDPI AG, 2023)
Individual differences in IBD illness severity, behavior, progression, and therapy response are evident. Since a break in the intestinal epithelial barrier causes IBD to begin, mucosal gene expression in IBD is crucial. Due to its high sensitivity and dynamic nature, molecular analysis of biomarkers in intestinal biopsies is feasible and provides a reliable means of evaluating localized inflammation. The goal of this investigation was to discover alterations in gene expression in the inflamed mucosa of IBD patients undergoing treatment with 5-amino salicylic acid (5ASA) (N = 39) or anti-TNF drugs (N = 22). The mucosal expression of numerous IBD-related genes was evaluated using qPCR. We discovered that the levels of the proteins Lipocalin-2 (LCN2), Nitric Oxide Synthase 2 (NOS2), Mucin 2 (MUC2), Mucin 5AC (MUC5AC), and Trefoil factor 1 (TFF1), which are overexpressed in untreated IBD patients compared to non-IBD subjects, are decreased by both therapy regimens. On the other hand, anti-TNF medicine helped the levels of ABCB1 and E-cadherin return to normal in IBD patients who were not receiving treatment.